2014
DOI: 10.4269/ajtmh.13-0457
|View full text |Cite
|
Sign up to set email alerts
|

Viral Isolates of a Novel Putative Phlebovirus in the Marche Region of Italy

Abstract: Abstract. Thirty pools from 900 (540 females and 360 males) Phlebotomus perfiliewi sandflies collected during the summer of 2012 in the Fermo area (Marche Region, central Italy) were tested for the presence of Phleboviruses. A nested polymerase chain reaction was performed using degenerated primers amplifying a fragment of the polymerase gene (large segment) and a fragment of the nucleoprotein gene (small segment) of the genus Phlebovirus. One pool was positive for Toscana virus, as expected from results of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…In the present study, dogs living in the Ionian island of Corfu showed a much lower seroprevalence compared to the human population living in the same island (3.9% vs 51.7%) [8]; however, in this case the techniques used were different; in the human study, ELISA/IIF detected not only TOSV IgG but also IgG raised after infection with other viruses belonging to the Sandfly fever Naples serocomplex in which 6 new viruses were described during the last decade (Arrabida, Fermo, Granada, Massilia, Punique, Zerdali) [16, 3337] in addition to Naples virus (a proven human pathogen) and Tehran virus. Although none of these viruses were detected or isolated in Greece or Cyprus, the presence of one of these 6 recently discovered viruses or of a yet to be discovered virus may account for these apparently discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, dogs living in the Ionian island of Corfu showed a much lower seroprevalence compared to the human population living in the same island (3.9% vs 51.7%) [8]; however, in this case the techniques used were different; in the human study, ELISA/IIF detected not only TOSV IgG but also IgG raised after infection with other viruses belonging to the Sandfly fever Naples serocomplex in which 6 new viruses were described during the last decade (Arrabida, Fermo, Granada, Massilia, Punique, Zerdali) [16, 3337] in addition to Naples virus (a proven human pathogen) and Tehran virus. Although none of these viruses were detected or isolated in Greece or Cyprus, the presence of one of these 6 recently discovered viruses or of a yet to be discovered virus may account for these apparently discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…Among the SFVs, only TOSV is related to neuro-invasive disease, while other sand-fly variants cause a mild flu-like illness, but the serological differentiation between the serotypes is very difficult and they are usually regarded as one serocomplex. In recent years, the geographical distribution of TOSV (or closely related other phleboviruses) has been extended dramatically within the old world and antigenically similar novel viruses have been reported [2,[15][16][17][18]. Therefore, our cases might represent a TOSV-related neuro-invasive strain, even though the immunofluorecsence assays were unable to distinguish between the viruses within the sand-fly virus serocomplex.…”
Section: Discussionmentioning
confidence: 86%
“…perniciosus colonies [37][38][39]. These experimental results were complemented by the observation in nature of equal rates of TOSV infection in male and female sand flies, suggesting the existence of transovarial (vertical) and/or venereal (horizontal) transmission during mating [40][41][42][43]. Additionally, the survival of TOSV in overwintering Ph.…”
Section: Pathways Of Tosv Transmission and Maintenancementioning
confidence: 83%